Simultaneous quantification of high-dose naloxone and naloxone-3-β-d-glucuronide in human plasma by UHPLC–MS/MS. (21st January 2019) - Kongstad, Kenneth T; Papathanasiou, Theodoros; Springborg, Anders D; Lund, Trine M; Werner, Mads U; Staerk, Dan
Aim: High-dose administration of the μ-opioid receptor inverse agonist naloxone (NX), has previously been demonstrated to reinstate nocifensive behavior in the late phase of inflammatory injuries. However, no current analytical methods can provide pharmacokinetic insight into the pharmacodynamic response of high-dose administration of NX.Materials & methods:  Based on protein precipitation using 50 μl human plasma, NX and naloxone-β-d -glucuronide (NXG) was analysed by UHPLC–MS/MS with 6 min cycle time. Results: A method for quantification of high-dose administered NX and NXG was developed and validated with intra- and interday precision and accuracy within ≤8.5% relative standard deviation (RSD) and -1.2–5.5% relative error (RE) for NX and ≤9.6% RSD and 0.6–6.5% RE for NXG. The method show excellent internal standard corrected matrix effects.Conclusion: A rapid UHPLC–MS/MS method was developed for quantification of NX and NXG in human plasma within 10–4000 ng/ml.